Classroom Popularity Hierarchy Predicts Prosocial and Aggressive Popularity Norms Across the School Year - Laninga-Wijnen L.; Harakeh Z.; Garandeau C.; Dijkstra J.; Veenstra R.; Vollebergh W. (Blackwell Publishing Inc., 2022)
This research is part of the Social Network Analyses of Risk behavior in Early adolescence (SNARE) study. Participating centers of SNARE include the Department of Sociology of the University of Groningen and the Utrecht Centre for Child and Adolescent Studies of the Utrecht University. SNARE has been financially supported by the Netherlands Organisation for Scientific Research (NWO) Vernieuwingsimpuls VENI grant project number 451‐10‐012, awarded to author Jan Kornelis Dijkstra (2010), and NWO Youth & Family Program project number 431‐09‐027, awarded to Wilma Vollebergh, Jan Kornelis Dijkstra, René Veenstra, & Zeena Harakeh (2010) and NWO‐Programming Council for Educational Research project number 411‐12‐027, awarded to René Veenstra, Wilma Vollebergh, Marijtje Van Duijn, Zeena Harakeh, Jan Kornelis Dijkstra, & Christian Steglich (2013). We thank the schools, teachers, and adolescents who participated in the SNARE project, and we are thankful that Aart Franken, Kim Pattiselanno, Loes van Rijsewijk, and Lydia Laninga‐Wijnen collected the SNARE data. We thank Assistant Professor and statistician Caspar van Lissa for his useful advices on our analyses.